Design of a Biomass Gasification Stove for Corn Cob Waste - Teguh Permadi; Budy Wiryono; Karyanik Karyanik; Asmawati Asmawati (Universitas Muhammadiyah Mataram, 2022)
Stoves are one of the technologies that play an important role in energy utilisation at the household scale. The utilisation of biomass waste as a fuel source is because the waste has a significant energy content. Based on BPS statistics for corn production in 2016, NTB province reached 1,278,271 tonnes and increased in 2017 to reach 2,127,324 tonnes, based on these data it is possible that corn will produce corn cobs that have the potential to be developed into bioethanol and bioenergy. The purpose of this study was to design and build a household scale corn cob waste biomass gasification stove, determine the effect of variations in air flow velocity on room temperature in the combustion process of corn cob waste, determine the comparison of water boiling temperatures at variations in air flow velocity of 5.0 m/s, 10.0 m/s, and 15.0 m/s. The research method used is experimental method by conducting experiments and performance tests in the Agricultural Workshop Laboratory. The research was conducted by varying the speed of air entering the reactor with speed variations of 5.0 m/s, 10.0 m/s and 15.0 m/s. The parameters observed include combustion chamber temperature, water boiling temperature, and initial ignition time. The results showed that the air velocity variation of 15.0 m/s affected the highest combustion temperature with 359.13 with 100 grams of ash, then the highest water boiling temperature was 60℃, and the initial ignition was recorded at 2:20:31 minutes. From the results of this study, it can be said that using the highest speed variation can produce perfect combustion.